THE EFFECT OF COMPETITION, EDUCATION AND TRAINING, JOB ROTATION, AND JOB PLACEMENT ON WORK QUALITY WITH INTERVENING COMMITMENT ORGANIZATION VARIABLES AT OFFICERTHE REGIONAL SECRETARIAT KARIMUN DISTRICT - Kurniawan, Ady; Indrayani, Indrayani; Khaddafi, Muammar; Catrayasa, I Wayan (RADJA PUBLIKA, 2022)
The purpose of this study was to determine and analyze the effect of competition, education and training, job rotation, and job placement on work quality with intervening organizational commitment variables at officerKarimun Regency Regional Secretariat. The method used is a questionnaire and distributed to 125 respondents. Analysis of statistical data using SEM PLS (Structural Equation Modeling Partial Least Square) and using path analysis to examine the pattern of the relationship between the influence of the dependent variable on the independent, both direct and indirect effects with SMART PLS 3.0 software. The results in the study indicate that competition has a positive and significant effect on organizational commitment with a p-value of 0.009 < 0.05, education and training have a positive and significant effect on organizational commitment with a p-value of 0.022 < 0.05, job rotation has a positive and significant effect on organizational commitment with a p-value of 0.016 <0.05, work placement has a positive and significant effect on organizational commitment with a p-value of 0.